Bibliometric analysis of digital transformation on organization design - Božić, Katarina (Anali Ekonomskog fakulteta u Subotici, 2025)
Digital transformation has become a key driver of change in modern organizations, reshaping their design and way of functioning. This paper aims to investigate how digitalization has impacted organizations and their organizational design, using a bibliometric approach to analyze research trends in this area. Using the Bibliometrix software package in the R programming language, bibliographic data analysis was performed in order to identify the most influential authors, key topics and future research directions. The study analyzed a dataset of 175 publications in English from the period 2000-2023, sourced from Web of Science Core Collection database, focusing on research articles discussing digital transformation and organizational design. Bibliometrix application was used to perform the bibliometric analysis, which included co-citation, keyword analysis, and thematic mapping to reveal core trends and influential papers in the literature. The study reveals that digital transformation significantly alters organizational structure and role distribution, often decentralizing power and increasing flexibility within companies. These findings align with theories on dynamic capabilities and suggest that further research could focus on how digital transformation supports agility in organizational design, providing practical insights for adapting organizations to digital era demands. Future research on the impact of digital transformation on organizational design could focus on artificial intelligence integration, digital skill requirements, hybrid structures, blockchain technology, as well as challenges and strategies for managing data security and privacy